Effects of Anticipation on Perception of Facial Expressions. Issue 1 (February 2014) - Ran, Guang Ming; Chen, Xu; Pan, Yan Gu; Hu, Tian Qiang; Ma, Jing
Human beings do not passively perceive the facial expressions of other people, but predict observed facial expressions by employing past experiences. The aim of the current study was to investigate whether and how anticipation affected the perception of facial expressions. A 3-way repeated-measures ANOVA on anticipation, orientation, and facial expression was performed on RTs and recognition accuracy in Experiments 1 and 2. The results showed that anticipation reduced susceptibility to negative facial expressions. In this regard, anticipation might be considered as an effective emotion-regulation strategy. In addition, a decreased inversion effect for positive facial expressions was found in the predictable condition, which might reflect a switch from feature-based to holistic processing.